Delay Minimization Topology Control in Planetary Surface Network: An Autonomous Systems Approach - Wei Zhang; Gengxin Zhang; Liang Gou; Bo Kong; Dongming Bian (International Journal of Distributed Sensor Networks)
This paper investigates the topology control problem in the planetary surface network (PSN) of Interplanetary Internet (IPN) using an autonomous system (AS) approach. We propose a delay minimization topology control (DMTC) algorithm to achieve low time delay and strong connectivity in the planetary surface network. Compared with the most existing approaches where either the purely centralized or the purely distributed control method is adopted, the proposed algorithm is a hybrid control method. In order to reduce the cost of control, the control message exchange is constrained among neighboring AS networks. We prove that the proposed algorithm could achieve logical k -connectivity on the condition that the original physical topology is k -connectivity. Simulation results validate the theoretic analysis and effectiveness of the DMTC algorithm.